Pelatihan Rekayasa Virtualisasi Rangkaian Kombinasional pada Sekolah Menengah Kejuruan Unggulan Husada - Hoiriyah Hoiriyah; Muhammad Saidi Rahman; Yusup Indra Wijaya; Muhammad Amin; Fakhriani Ekawati (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Informatics is a subject that is desired to be able to contribute computational thinking skills based on logic, as well to the ways to think in solving a problem more effectively, efficiently and optimally in various fields of life that are now inseparable from the use of computers also provides technological skills where the binary system has several basic gates, namely NOT, AND and OR which are basic gates have symbols, truth tables, and gates that must be remembered and balanced according to the provisions in Boolean algebra, Basically students have difficulty understanding it because the teacher's method when delivering the material still uses the method of delivering practice, group work, lectures, questions and answers, and short quizzes. However, the practice carried out in this class only describes the input of the truth table which is depicted on the board and after that the basic gate is made using symbols, so this training is carried out to improve the skills of students who get an 85% increase and are categorized as being able to implement and are stated to have increased in Skill.